Orbital synchronization capture of two binaries emitting gravitational waves. Issue 1 (26th December 2017) - Seto, Naoki
Abstract: We study the possibility of orbital synchronization capture for a hierarchical quadrupole stellar system composed by two binaries emitting gravitational waves. Based on a simple model including the mass transfer for white dwarf binaries, we find that the capture might be realized for inter-binary distances less than their gravitational wavelength. We also discuss related intriguing phenomena such as a parasitic relation between the coupled white dwarf binaries and significant reductions of gravitational and electromagnetic radiations.